Micro-Teaching Video as Assignment for Indonesian EFL University Students; Exploring Pre-Service Teachers’ Self-Efficacy - Dwi Budidarma Sutrisno; Jasmal Martora; Megawati Basri (Universitas Khairun, 2024)
This qualitative research aims to explore perspectives from Indonesian EFL pre-service teachers about their self-efficacy through micro-teaching video assignment. The data were collected from observation, questionnaire, and written reflection taken from 19 participants of first, second, and third year university students in an English language education study program at one of the private universities in North Maluku. The collected data then went through thematic analysis. The results show that the students’ approaches to the instruction of creating micro-teaching are varied, while the students’ performance is influenced by limited vocabulary, grammar issues and subject matter comprehension, and finally students’ reflections include challenges and languages used in micro-teaching videos as well as their self-efficacy consisting their learnings, realizations, and beliefs. In other words, findings from current study contribute to further discussion related to teacher training courses and possible practical approaches.